Fast Professors, Research Funding, and the Figured Worlds of Mid-Career Ontario Academics - Sandra Acker; Michelle K McGinn (Brock University, 2021)
Heightened pressures to publish prolifically and secure external funding stand in stark contrast with the slow scholarship movement. This article explores ways in which research funding expectations permeate the "figured worlds" of 16 mid-career academics in education, social work, sociology, and geography in 7 universities in Ontario, Canada. Participants demonstrated a steady record of research accomplishment and a commitment to social justice in their work. The analysis identified four themes related to the competing pressures these academics described in their day-to-day lives: getting funded; life gets in the way; work gets in the way; and being a fast professor. Participants spoke about their research funding achievements and struggles. In some cases, they explained how their positioning, including gender and race, might have affected their research production, compared to colleagues positioned differently. Their social justice research is funded, but some suspect at a lower level than colleagues studying conventional topics. In aiming for the impossible standards of a continuously successful research record, these individuals worked "all the time." Advocates claim that slow scholarship is not really about going slower, but about maintaining quality and caring in one's work, yet participants' accounts suggest they have few options other than to perform as "fast professors." At mid-career, they question whether and how they can keep up this pace for 20 or more years.